Development of a multi-historian SCADA data collection middleware : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Computer and Electronic Engineering at Massey University, Albany, New Zealand. - Bridges, Jeffrey Paul (Massey University, 2013)
This thesis details the implementation of a SCADA middleware package designed to provide a common interface to the most commonly used SCADA historians in use within local government in New Zealand. The middleware integrates with a New Zealand developed cloud based solution that is used throughout the country for compliance monitoring and reporting of water and wastewater treatment facilities. The middleware connects via the internet to the historians hosted on-site within council networks and retrieves data which is replicated in a local database. This approach provides backup for the data and allows it to be accessed quickly when required for reporting. The middleware database is hosted within a Microsoft SQL Server instance to ensure compatibility and ease of rollout when paired with the commercial cloud solution. To ensure reliable data collection and resilience to connection interruption all transactions made against the client historians are controlled by a queue stored in the middleware database. The middleware includes an inbuilt mechanism for integrity checking to ensure all data available in the client historian is collected and has been designed to run with minimal intervention of company staff. To reduce storage requirements the middleware includes a data deduplication system that removes repeated samples from the SQL Server database after integrity checking has been performed. This provides a lossless compression mechanism that does not alter the precision of the data collected. The middleware implementation has now been in use in a production environment collecting data from councils for compliance purposes for approximately six months. During this time data collection has been very reliable with the middleware handling numerous connection outages without intervention.
Keywords: Automatic data collection systems; Supervisory control systems; Water treatment plants; Sewage disposal units; Automation